KINERJA KARYAWAN CV RAJAWALI INTI SUKSES DI MASA NEW NORMAL - Fatimah Zahro Ijabi; Pardi Pardi (Bajang Institute, 2022)
This study aims to review the performance of accounting employees at CV Rajawali Inti Sukses during the New Normal. Where this period is a new transition period for companies that have just adapted to the pandemic. The method used by the researcher is a qualitative descriptive. Data collected through in-depth interviews with accounting employees at CV Rajawali Inti Sukses. With the results that can be concluded by the researcher is the division of tasks and authority in the implementation of the administration has been good and smooth. With a positive assessment and motivation from the head of the section is a manifestation of good performance. Then the accounting employees at CV Rajawali Inti Sukses have expertise in their fields